Transformational Leadership in Enhancing Public Service Quality in the Digital Era - Andi Herlina; Hamka Hamka (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to analyze the role of transformational leadership in improving the quality of public services in the digital era. It examines how transformational leadership supports digital transformation, service innovation, and citizen-oriented public service delivery. Design/methodology/approach – This study adopts a qualitative approach with an interpretative case study design. Data were collected through in-depth interviews and observations involving purposively selected civil servants (ASN) at a local government agency in Makassar City. The data were analyzed using thematic analysis. Findings – The findings reveal that transformational leadership enhances public service quality by fostering a digital transformation vision, encouraging service innovation, and promoting more responsive and citizen-oriented behaviors among public officials. It also creates a work environment that is adaptive to technological change. However, its implementation is constrained by limited digital competencies, resistance to change, and technical challenges in digital service systems. Originality/Value – This study highlights transformational leadership as a critical driver of public service quality in the digital era. It contributes to the public administration literature by emphasizing the importance of integrating leadership, human resource capacity development, and digital infrastructure to achieve sustainable, citizen-centered public services.